The Relationship Between Physical Activity in Physical Education and Adolescents' Psychological Well-being - Sahwa, Sahwa (Journal of Salutare, 2024)
Physical education plays an important role in the physical and mental development of adolescents. This article aims to analyze the relationship between physical activity in physical education and adolescent psychological well-being. Based on a qualitative approach, this study involved participant observation and in-depth interviews with high school students in three schools in Jakarta. The results showed that active participation in physical activities contributed significantly to improving mood, reducing stress, and increasing students' self-confidence. Physical activity carried out routinely in physical education also strengthened social relationships between students, which had positive implications for overall psychological well-being. These findings emphasize the importance of optimizing physical education learning as a means of improving adolescent mental health. This article recommends the integration of fun and participatory physical activities into the school curriculum to support students' psychological well-being.